ChemInform Abstract: Methyltrioctylammonium Chloride Catalyzed Sonochemical Synthesis of Acridine Diones. Issue 8 (25th February 2014) - Kaur, Bhupinder; Kumar, Harish
Abstract via a three‐component reaction